Online communication and sustainability reporting: the managerial issues - Nazahah Rahim,; Noorain Omar, (Penerbit Universiti Kebangsaan Malaysia, 2017)
The use of online communication to disclose sustainability efforts is becoming widespread especially in the technological advancement era. It involves communicating any sustainability related information via the internet, particularly on websites. There are managerial issues associated with the initiative use of online communication for sustainability reporting, even though it brings many benefits to companies in terms of increased transparency, reputation, trust, information accuracy, faster information dissemination and many more. In addition to this, the level of sustainability reporting via online communication is found to be low, which means that this communication method is not well utilized. Therefore, this study aims to uncover the opinions of managers towards using online communication to report sustainability efforts and the managerial issues associated to it. As sustainability reporting is common among public listed companies, 10 semi-structured interviews were conducted with managers of various backgrounds from these companies. The results revealed that the fostering of sustainability reporting via online communication was viewed as a positive effort from the perspective of respondents; however, there were some managerial issues. These issues are categorized as leader’s confidence, personal constraints and external factors. Most reporting and disclosure studies focus on performance metrics and other data driven factors, whereas this study took a different leap in focusing on managers, who are also the corporate players. Hence this study provides a new insight on online communication, focusing on how organizational leaders can have an impact on the setting of sustainability reporting and the dilemmas they are facing.